Undocumented Crime in Juan Mayorga’s Animales nocturnos - Jeffrey K. Coleman (Studies in 20th & 21st Century Literature, 2019)
The link between criminality and immigration is often personified in the undocumented immigrant. As nations have constricted the flow of immigrants, laws have inscribed a criminal culpability attached to the lack of documentation. The lack of papers becomes such a part of their persona that in Spanish the colloquial term for an undocumented immigrant is a sin papeles ‘illegal immigrant.’ Juan Mayorga’s chilling 2003 play Animales nocturnos (Nocturnal) explores the lengths to which laws can be used to criminalize and psychologically abuse undocumented immigrants. This paper will explore how immigration law manifests itself in the play and how said manifestation establishes a Hegelian power dynamic between the autochthonous and immigrant protagonists of the play that results in the rewarding of criminal behavior. In order to demonstrate how the law leads to exploitation, textual analysis of Spain’s immigration law will be juxtaposed to Hegel’s master-slave dialectic. The juxtaposition will show that Spain’s law does not give immigrants, regardless of status, the ability to fight against exploitation without putting themselves at risk of deportation, thus creating a catch-22 that enables autochthonous exploiters to take advantage of an immigrant’s lack of legal residency status.
Keywords: Juan Mayorga; Animales nocturnos; immigration; Hegel